Rhytidectomy with tunneling combined with liposuction and reduced detachment - Guilherme de Castro Greco Guimarães; Márcio Greco Guimarães (Revista Brasileira de Cirurgia Plástica)
INTRODUCTION: Multiple facial rejuvenation techniques have been used to obtain satisfactory results with minimal complications. With the introduction of liposuction for facial surgery, treatment of the cervical region has improved. This study aimed to describe a technique using preceding liposuction combined with reduced detachment and plication of the superficial muscular aponeurotic system/platysma for treatment of facial aging. METHODS: We retrospectively analyzed the results in 129 patients who underwent surgery between 2005 and 2015. RESULTS: The patients reported satisfaction with the surgical technique, a low complication rate, and early return to work. CONCLUSIONS: Rhytidectomy with tunneling combined with liposuction and selective detachment is effective, with good mobility of the overlying skin flap; the technique is safe and reproducible, and is an option for the treatment of facial aging.